Causal relationship between circulating immune cells and the risk of type 2 diabetes: a Mendelian randomization study - Li, Jin; Niu, Qingmin; Wu, Aiwei; Zhang, Yuchu; Hong, Liquan; Wang, Hu (Frontiers in Endocrinology, 2023)
Objectives: Though type 2 diabetes (T2D) has been known a metabolic disease caused by multiple factors, the etiology remains insufficiently understood. Here we aimed to figure out whether circulating immune cell profiles causally impact on T2D liability. Methods: We applied one genome-wide association studies (GWAS) summary statistics of blood traits in 563,085 participants from Blood Cell Consortium and another GWAS of flow cytometric profile of lymphocyte subsets comprising 3,757 Sardinians to identify genetically predicted blood immune cells. We also obtained GWAS summary statistics in 898,130 individuals from DIAGRAM Consortium to evaluate genetically predicted type 2 diabetes (T2D). We primarily used inverse-variance weighted (IVW) and weighted median methods to perform mendelian randomization analyses and sensitivity analyses to evaluate heterogeneity and pleiotropy. Results: For circulating blood leukocyte and its subpopulations, the increase of genetically predicted circulating monocyte count were causally correlated with higher risk of T2D [odds ratio (OR)=1.06; 95% confidence interval (CI)=1.02-1.10, p=0.0048]. For lymphocyte subsets, CD8+ T cell and CD4+ CD8dim T cell count were identified with causal effect on T2D susceptibility. (CD8+ T cell: OR=1.09, 95% CI=1.03-1.17, p=0.0053; CD4+ CD8dim T cell: OR=1.04, 95% CI=1.01-1.08, p=0.0070). No pleiotropy was determined. Conclusions: These findings demonstrated that higher circulating monocyte and T lymphocyte subpopulation predicted increased T2D susceptibility, which confirmed the immunity predisposition for T2D. Our results may have the potential to provide new therapeutic targets for the diagnosis and treatment of T2D.